A Qualitative Study on Nurses’ Experiences of Reporting Patient Safety Incidents in East Nusa Tenggara, Indonesia - Siga Tage, Petrus Kanisius; Berkanis, Appolonaris T; Betan, Yasinta; Pinis, Elisabet Batseba (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Reporting patient safety incidents is important to improve patient safety and quality of care. Barriers to report patient safety incidents in nursing may occur due to lack of knowledge and unscheduled as well as low reporting rates. Unfortunately, nurses’ experiences in reporting patient safety incidents have not been comprehensively reviewed.Purpose: The purpose of this study was to explore nurses’ experiences of reporting patient safety incidents in East Nusa Tenggara, Indonesia.Methods: A descriptive phenomenological approach was used to identify, analyze and describe the experiences of 15 nurses in reporting patient safety incidents. Nurses having worked for more than two years, not on leave, not being infected with COVID-19 in the last 14 days, and not having a structural position were purposively recruited. Data were collected using in-depth interviews and voice recordings. The collected data were then transcribed verbatim, and thematic analysis was applied for data analysis.Results: Four main themes were found in this study, which included: (1) Priority and responsibility for services, (2) Barriers to incident reporting, (3) Learning for nurses, and (4) Support for nurses.Conclusion: The nurses experience of in reporting safety incidents is still constrained by several obstacles. It is hoped that health care organizations need to provide appropriate strategies to enhance the safety incident reporting efforts made by nurses. Based on the research findings, it is recommended that health service organizations disseminate the use of safety incident reporting forms and assist nursing managers to their subordinates by conducting supervision and motivation related to incident reporting on a scheduled and continuous basis.